2010
DOI: 10.1111/j.1742-7843.2010.00616.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Blood and Serum Lead Levels in Peripartum Women and their Respective Umbilical Cords

Abstract: Foetal exposure to lead (Pb) during pregnancy is a major problem. However, no previous study has examined whether Pb concentrations in blood (Pb-B) and in serum (Pb-S) from pregnant women correlate with Pb-B and Pb-S in the foetuses. This hypothesis was tested in the present study. We measured Pb-B and Pb-S in 120 healthy pregnant women (more than 38 weeks of gestation) and their respective umbilical cord samples. The analyses were carried out with an inductively coupled plasma mass spectrometer. We found high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 27 publications
2
19
0
3
Order By: Relevance
“…We found a statistically significant association at each time point. Previous studies of women with higher blood lead have yielded similar results [30,33,34] with observed correlations between cord and maternal blood lead of r 2 = .57 and r 2 = .63 [34]. Those correlation values are within a reasonable range of the correlations observed in the present study for the second and third trimesters (r 2 = .74 and r 2 = .83, data not shown).…”
Section: Discussionsupporting
confidence: 93%
“…We found a statistically significant association at each time point. Previous studies of women with higher blood lead have yielded similar results [30,33,34] with observed correlations between cord and maternal blood lead of r 2 = .57 and r 2 = .63 [34]. Those correlation values are within a reasonable range of the correlations observed in the present study for the second and third trimesters (r 2 = .74 and r 2 = .83, data not shown).…”
Section: Discussionsupporting
confidence: 93%
“…Lead can cross the placenta and expose the fetus to the harmful effects of this toxic, thus affecting the embryonic development of multiple organs and causing neurobehavioral impairments in infancy and early childhood [4, 5, 9, 17]. Therefore, pregnancy is considered a critical time for exposure to lead for the mother and the fetus [14, 18]. …”
Section: Introductionmentioning
confidence: 99%
“…Lead readily crosses the placenta, with a fetal : maternal ratio of about 0.7–0.9,46 but studies on the association of blood lead levels in pregnancy and a variety of measures of birth outcomes, including birthweight (BW), head circumference (HC), gestational age at delivery and preterm delivery, have had inconsistent results at all levels of exposure 711. Poor birth outcomes are known to be associated with poor developmental trajectories in infancy, as well as having long-term implications for adult health 1214.…”
Section: Introductionmentioning
confidence: 99%